KAJI EKSPERIMENTAL PENGARUH BAFFLE PADA ALAT PENUKAR PANAS ALIRAN SEARAH DALAM UPAYA OPTIMASI SISTEM PENGERING - Azwinur Azwinur; Zulkifli Zulkifli (University of Muhammadiyah Jakarta, 2019)
Heat exchangers or heat exchangers are tools used to change the temperature of the fluid or change the fluid phase by exchanging heat with another fluid. In a heat exchanger, the ability to exchange heat is largely determined by the type of fluid flow and fluid passing through the heat exchanger. The use of heat exchangers in the field of drying is now a necessity to overcome the problems of drying productivity. The purpose of this study was carried out to determine the effectiveness of the heat exchanger experimentally based on directional flow by comparing construction using baffle and without using baffle in an effort to optimize the drying system. The research method was carried out by fabricating 2 units of heat exchangers and by field testing. The test data obtained are the input and output temperatures of the heating fluid flow and cooling fluid flow and flow velocity. Based on preliminary research data shows that the use of baffle affects the increase in temperature on the heat exchanger, where at the fresh air outlet that does not use baffle produces a temperature of 72oC while the baffle produces 88oC with the Log Mean Temperature Difference heat exchanger without using a baffle higher than heat exchanger that uses a baffle guide blade. This can illustrate that the smaller heat losses are wasted so that the absorption of heat by the reverse system will be higher.